2011
DOI: 10.3109/00365521.2011.574725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-invasive assessment to diagnose liver fibrosis in chronic hepatitis B and C patients

Abstract: HA, APRI, FibroTest, Fib-4, and TE reliably distinguish non-cirrhotic and cirrhotic patients. Except for MBT, all tests discriminate between mild and moderate fibrosis. As single tests: FibroTest, Fib-4, and TE were the most accurate for detecting early fibrosis; combining different non-invasive tests increased the accuracy for detection of liver fibrosis to such an extent and thus might be acceptable to replace liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 41 publications
2
32
0
3
Order By: Relevance
“…Studies that were judged as low risk of bias or unknown in the three most important QUADAS domains, namely patient selection, index test and reference standard, were still a modest fraction of the total number of studies (29 out of 152; 19%). 72,73,79,80,86,91,92,106,110,133,135,143,148,165,167,173,[197][198][199]201,203,[206][207][208]211,214,215,221,222 We explored potential sources of heterogeneity as outlined in the methods section. As all but five studies were of low methodological quality, 86,127,143,186,222 this potential source of heterogeneity could not be assessed.…”
Section: Results: Hepatitis C Virusmentioning
confidence: 99%
“…Studies that were judged as low risk of bias or unknown in the three most important QUADAS domains, namely patient selection, index test and reference standard, were still a modest fraction of the total number of studies (29 out of 152; 19%). 72,73,79,80,86,91,92,106,110,133,135,143,148,165,167,173,[197][198][199]201,203,[206][207][208]211,214,215,221,222 We explored potential sources of heterogeneity as outlined in the methods section. As all but five studies were of low methodological quality, 86,127,143,186,222 this potential source of heterogeneity could not be assessed.…”
Section: Results: Hepatitis C Virusmentioning
confidence: 99%
“…A number of studies have explored the feasibility of using non-invasive tests to predict cirrhosis. These include the Fibroscan and FibroTest-ActiTest, galactose and methacetin breath tests, TE, fibrotest, cirrhosis discriminant score, AST/ALT ratio, APRI, FIB-4 and AP index (24)(25)(26)(27)(28)(29). However, certain tests are impractical to use in a clinical setting since they require expensive instrumentation or may use less common biochemical markers, including α2-macroglobulin, haptoglobin and apolipoprotein A1, or the use of specialized software for computations.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially validated primarily in Caucasian populations with CHC and the results showed a good correlation with liver fibrosis stage [18], [19], [20]. However, in contrast to TE, only a few studies have been reported to date in patients with CHB [21], [22], [23], [24], [25]. In particular, the investigation focusing Asian population with CHB has been extremely scarce.…”
Section: Introductionmentioning
confidence: 99%